Parental Relationships, Peer Interaction, and Ease of Access to Obtaining Cigarettes on Smoking Habits in Adolescents in the PGRI Cikampek Vocational School Environment in 2024 - Nadya Rachmadayanti; Sudiono; Agus Subari; Rima Novianti (INDOGENIUS, 2026)
Background & Objective: This study aims to analyze the factors that influence smoking habits among teenagers in Vocational High Schools (SMK). This research explores the relationship between variables such as parental relationships, peer interactions, and ease of access to cigarettes. Method: This research is a quantitative descriptive analytic correlational research with a retrospective case control design using survey and questionnaire methods distributed to 86 respondents. The validity test results show that all items in the questionnaire are declared valid, with a calculated r value that is greater than r TABLE. Apart from that, the reliability test using Cronbach's Alpha produced a value above 0.60, which shows the questionnaire is reliable. Result: Analysis of parental closeness, peer interaction, and ease of access to cigarettes have a significant role in shaping smoking habits among teenagers. Conclusion: These findings highlight the importance of interventions that are more focused on vocational school adolescents, as well as the need for a holistic approach involving parents and the social environment to reduce the prevalence of smoking among adolescents. It is hoped that this research will provide insight for educators and policy makers in designing more effective prevention strategies.